Analisis Perubahan Penggunaan Lahan pada Wilayah Pesisir Pantai Liang Kecamatan Salahutu Kabupaten Maluku Tengah - Fitria Tella; Daniel Anthoni Sihasale; Melianus Salakory (GEOFORUM, 2025)
Land use changes in coastal areas are increasingly complex due to population growth, economic activities, and tourism development. This condition is evident in Liang Beach, Salahutu District, Central Maluku Regency, where land conversion pressures occur between natural ecosystems and development needs. This study aims to identify and analyze land use change dynamics during 2021–2024. The research employed a quantitative-descriptive approach using Google Earth Pro satellite imagery combined with field observations at ten coordinate points. The findings reveal a decline in natural vegetation from 45% to 30%, an increase in economic-use land from 15% to 25%, and the expansion of tourism areas from 10% to 20%. Water bodies and open land decreased by 2–3%. These results highlight a spatial shift from ecological to economic functions, implying higher abrasion risks, biodiversity loss, and potential stakeholder conflicts. The study concludes that integrated coastal management is crucial, requiring policy alignment, mapping technology, and community involvement to sustain ecological and socio-economic balance. It recommends adopting environmentally adaptive spatial planning and sustainable tourism strategies for Liang Beach